When Even Listening to Music, Dancing, and Escaping from Auditoriums is Educational: Ethnomusicology at the Faculty of Humanities - Mára, Jaromír (Lidé města, 2015)
According to the head of the program doc. Zuzana Jurková, the evolution of ethnomusicology at our faculty is progressing like a partly-controlled improvisation. “I started out with just a couple of overview courses. Now it is an all-round proper program. This semester we opened 15 courses, out of which eight were led in English by lecturers such as prof. Shelemay from Harvard University, prof. Reyes from Columbia University, or prof. Radulescu from Universitatea Națională de Muzică in Romania. Last year, we published a book entitled Pražské hudební světy, whose English version Prague Soundscapes was distributed by Chicago University Press. And we also held an international conference whose materials are in print at the moment,” says docent Jurková adding that in her opinion, “There is no university-level ethnomusicological program in Europe that is this dynamic.” Ethnomusicological courses at FoH predominantly focus on the music of the marginalized and on urban spaces. The approximate form of education of future ethnomusicologists is indicated by the recently concluded summer school of Jewish music.